Modern methods of computer-related fraud: legal characteristics and qualification - Kryshevych, Olga; Andrushchenko, Igor; Striltsiv, Olexandr; Pyvovar, Yuriy; Rivchachenko, Olena (Cuestiones Políticas, 2021)
Due to the spread of new methods of committing fraudulent actions using electronic devices, the problem arose to provide you with adequate characteristics of criminal law for the development of measures leading to counteracting such crimes. The objective of the article was to identify common methods in Ukraine of committing fraud using computers, to assess the characteristics of criminal law that these crimes have, and, in turn, to determine measures to counter them. Methodologically, this is a documentary investigation. The scientific novelty of the study’s findings was to identify methods of performing fraudulent actions using electronic computers that will improve the legal qualification of crimes and affect the prosecution of persons guilty of committing such illegal actions. Measures to prevent such criminal offences were also developed. The results of the study help improve the work of law enforcement agencies in Ukraine, in determining recurrent methods of committing fraudulent actions using electronic means and their proper qualification, providing an opportunity to prosecute those who commit such illegal actions and develop ways for cybercrime research and prevention in general.